ANALISIS KELAYAKAN EKONOMI USAHATANI JAGUNG POLA AGRISILVIKULTUR PADA SISTEM AGROFORESTRI DI DUSUN GIWANG DESA RAYUNG KECAMATAN SENORI KABUPATEN TUBAN - Isna Agustina Safira; Pawana Nur Indah; Nisa Hafi Idhoh Fitriana (Fakultas Pertanian, Universitas Janabadra, 2023)
This study aimed to identify the pattern of corn farming partnerships between Perhutani and farmers, analyze the average cost, income, and income of corn farming with agrisilvicultural patterns in agroforestry systems, and analyze the economic feasibility of corn farming with agrisilvicultural patterns in agroforestry systems. in Giwang Hamlet, Senori District, Tuban Regency. This research took place in Giwang Hamlet, Rayung Village, Senori District, Tuban Regency, especially in the BKPH Malo forest area, KPH Parengan. The method of determining the sample using probability sampling technique with the Propotionate Stratified Random Sampling method obtained as many as 62 respondents. Methods of data analysis in this study using descriptive analysis, cost analysis, and feasibility analysis. The results of this study indicate that the partnership pattern carried out by farmers and Perhutani was a profit-sharing system on land that has been utilized by farmers, namely on forest land owned by Perhutani in accordance with Perhutani 307/042.3/OPS/DIR/2020 concerning the 2020 Agroforestry Policy. The total cost of farming Corn is IDR 9,308,408. The income from agrisilvicultural corn farming in Giwang Hamlet is IDR 6,853,377. Income IDR 16,229,387. The feasibility level of R/C agrisilvicula maize farming is 1.74, meaning that farming was feasible and profitable and the BEP Production, Revenue BEP, and Price BEP values have exceeded the breakeven point so that corn farming with an agroforestry system can be said to be profitable. INTISARIPenelitian ini bertujuan untuk (1) Mengidentifikasi pola kemitraan usahatani jagung antara Perhutani dan petani,(2) Menganalisis rata-rata biaya, penerimaan dan pendapatan usahatani jagung pola agrisilvikultur pada sistem agroforestri, dan (3) Menganalisis kelayakan ekonomi usahatani jagung pola agrisilvikultur pada sistem agroforestri di Dusun Giwang Kecamatan Senori, Kabupaten Tuban. Penelitian ini bertempat di Dusun Giwang, Desa Rayung, Kecamatan Senori, Kabupaten Tuban khususnya di wilayah hutan BKPH Malo, KPH Parengan. Metode penentuan sampel menggunakan teknik probability sampling dengan metode Propotionate Stratified Random Sampling didapatkan responden 62 orang. Metode analisis data menggunakan analisis deskriptif, analisis biaya, dan analisis kelayakan. Hasil penelitian menunjukkan bahwa pola kemitraan yang dilakukan petani dan Perhutani adalah sistem bagi hasil atas lahan yang telah digunakan oleh petani yaitu pada lahan hutan milik Perhutani sesuai dengan Perhutani 307/042.3/OPS/DIR/2020 perihal Kebijakan Agroforestry tahun 2020. Total biaya usahatani jagung Rp 9.308.408, Pendapatan usahatani jagung pola agrisilvikultur di Dusun Giwang Rp 6.853.377, Penerimaan Rp 16.229.387. Tingkat kelayakan R/C usahatani jagung pola agrisilvikulur sebesar 1,74 maka usahatani layak dan menguntungkan dan nilai BEP Produksi, BEP Penerimaan, dan BEP Harga telah melampaui titik impas sehingga usahatani jagung dengan sistem agroforestri dapat dikatakan untung.